FRI0401 IMPLEMENTATION OF NICE GUIDELINES FOR OSTEOARTHRITIS IN PRIMARY CARE. FEASIBILITY STUDY OF JIGSAW-E IN SCOTLAND. (2nd June 2020) - Frost, H.; Cowie, J.; Tooman, T.; Dziedzic, K.
Abstract : Background: In the UK osteoarthritis (OA) is a common musculoskeletal problem with 8.75 million people seeking treatment in 2015 1. Evidence-based guidelines are available for the management of OA but implementation into routine daily practice remains complex. The Joint Implementation of Guidelines for Osteoarthritis in Western Europe (JIGSAW-E) model of care was developed and evaluated in England and implemented in Europe with an aim to optimise quality primary care for OA, support self-management and promote use of NICE guidelines 2 . The intervention includes: 1. An OA guidebook for patients 2. A model OA consultation for primary care 3. Training for practitioners to deliver the model consultation 4. Measures of quality care using an e-template Objectives: To explore the feasibility of implementing the JIGSAW-E model to support people with OA in Scottish primary care. Research questions were informed by the Theoretical Domains Framework with an aim of: 1) Exploring knowledge and beliefs about OA and its management in primary care. 2) Identifying determinants for change; barriers and facilitators to implementing the JIGSAW-E model in Scotland. Methods: This qualitative study was comprised of 2 phases: Phase 1 included semi-structured interviews with health professionals (GPs and Extended Scope Practitioners) working in primary care. A purposeful sampling approach aimed to provide geographical and professional representation across Scotland. Interviews were recorded, transcribed and analysed using a theoretically-informed thematic framework approach. Phase 2 involved an engagement workshop that allowed for refinement and direct validation of emergent findings. Results: 90 invitations were sent to practice managers in primary care. 14 participants from 10 practices across 6 Health Boards in Scotland were recruited for interviews, including 6 GPs and 8 Physiotherapy Extended Scope Practitioners (ESPs). 23 participants attended the engagement workshop (ESPs = 22, GPs =1). Thematic analysis indicated four main themes related to the research questions: 1) Most participants were aware of NICE guidelines and believed they provided evidence-based OA care, and yet, for example, prescribing of co-codamol remained high. Physiotherapy ESPs were more likely to follow OA guidelines than GPs. 2) Adaptations of the JIGSAW-E model are needed to support OA management in the Scottish context. For example, in addition to adapting the guidebook for local relevance, the e-template was met with resistance due to technological barriers. 3) System-based barriers to implementation of the JIGSAW-E model included; lack of overall time for external training for practitioners; limited time in GP/patient appointments to consult and explain medication use and importance of physical activity. In part because patients usually present with multi-morbidities. 4) The roll out of ESPs across Scotland in primary care provides a potential key for the delivery of sustainable evidence-based care in the Scottish health system. Conclusion: Overall, participants were in favour of the JIGSAW-E model in Scotland. Contextual adaptation of written materials would increase acceptance, ownership and usability by both practitioners and patients. The evolving role of GPs and ESPs is key to implementation, where ESPs provide leadership in the delivery of evidence-based care for patients with osteoarthritis. References: [1]Arthritis Research UK. State of Musculoskeletal Health 2017. [2]Dziedzic KS et al. Implementation of musculoskeletal Models of Care in primary care settings: Theory, practice, evaluation and outcomes for musculoskeletal health in high-income economies. Best practice & research Clinical rheumatology 2016;30(3):375-97. Acknowledgements: Thanks are due to the JIGSAW-E team, all participants, SISCC and EIT for funding. Disclosure of Interests: None declared